Incidence of Cancer: Alarming Numbers - Annia Lourdes Iglesias Armenteros; Ada Elva Suárez Rodríguez (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
Cancer is an important health problem worldwide. It affects all of the countries, independently of the race, culture, level of economical development and political system. Around 10 million of new cases of cancer are detected every year. At present approximately 50 000 women died because of this disease.